LECTOTYPIFICATION OF SCUTELLARIA GLABRATA (LAMIACEAE) (Scientific journal of the Fergana State University, 2024)
During our literature review and herbarium studies, we encountered a typological issue regarding the name Scutellaria glabrata. In this study, the nomenclature history of Scutellaria intermedia var. glabriuscula Popov is presented, and lectotypification of S. glabrata is proposed.